APLIKASI COMMUNITY GOVERNANCE DALAM PENGELOLAAN PROGRAM PENANGGULANGAN KEMISKINAN - KUSHANDAJANI, KUSHANDAJANI (Politika: Jurnal Ilmu Politik, 2013)
This research is motivated by the deepen concern toward the concept of communitygovernance. There is a paradigm change in public administration, from government togovernance. That paradigm encourage many changes in public administration, includedprograms of poverty reduction. When community claim any services that local governmentcan not fulfill it, communities effort to make self-supporting and play along to each other tofulfill their requirement. So, it’s important thing to develop commmunity governance as amodel to manage programs of poverty reduction. The main purpose this research is todescribe the application of community governance in PNPM-MP (Program NasionalPemberdayaan Masyarakat-Mandiri Perkotaan). Result this research describes that BKMMatra as community can do the function of governance, e.g: Community Leadership,Community Empowerment, and Community Ownership. Application of Communityleadership can be seen in developing shared visions and understandings , communityparticipation, and co-operative behaviours. Application of Community Empowerment can beseen in how comunity access to resources, do power sharing, and decentralize of decisionmaking.Realization of Community Ownership can be seen in how community developsense of belonging, sense of caring, and valuing diversity.Keywords: community governance, community leadership, community empowerment,community ownership.A. PENDAHULUAN